Implikasi Hukum Dalam Membuat Akta Jaminan Hutang Berdasarkan Surat Keputusan Pegawai Negeri Sipil Yang Statusnya Diberhentikan - Wirawan, Sherin Nisa (Officium Notarium, 2024)
This study was conducted to determine the opportunities for financing institutions to provide credit facilities in making debt guarantee deeds based on the decree of dismissed civil servants. How are the legal implications of making debt guarantee deeds based on the decree of dismissed civil servants? Second, how is the legal protection of creditors due to debt guarantee deeds based on the decree of dismissed civil servants? This study uses a normative method that examines laws and regulations relevant to the problem studied and interviews with financing institutions as the authorities in resolving obstructed credit problems. The results of the study indicate that the legal implications of making debt guarantee deeds based on the decree of dismissed civil servants are that they cause creditors to suffer losses if the credit is paid in default or not smoothly. Second, creditors provide legal protection by adding collateral so that debtors are more obedient in performing their obligations.